Controle e inovação: desafios de inovar no laboratório pela perspectiva do design - Nascimento, Bianca Moraes do (Universidade do Vale do Rio dos Sinos, 2025)
Design is an area of innovation, and organizations create departments to develop innovations based on design. The practice of design requires a certain amount of freedom to create something new and is also related to originality - values that seem to clash with the organization’s controlled nature. The innovation sought by organizations is often defined in terms of capital growth, market expansion, and investment, rather than risk. Therefore, in the corporate reality, it is unthinkable that a project could arise from an uncontrolled creative act. This paradox - between control and innovation in a corporate environment designed to foster innovation, such as an innovation laboratory - shapes the objective of this research: to understand how design can explore the relationship between control practices and innovation processes from the perspective of innovation laboratories. To achieve this, the objective is broken down into: understanding how control practices manifest in the field of design through a literature review; characterizing innovation from the perspective of the organization, design, and laboratory in the literature; understanding how control manifests and impacts the organizational environment of the innovation laboratory, from the perspective of professionals working in these spaces; and proposing challenges for the design field to intentionally shape innovation projects within the organizational environment of innovation laboratories. At this stage, the research presents a literature review addressing topics such as control; control in design; organizational innovation; innovation through design; and innovation in laboratories. It also discusses the methodology adopted for the fieldwork, which involved interviews with seven professionals who worked in five innovation laboratories of large Brazilian companies. The analysis of the results revealed eleven forms of control observed in the innovation processes developed in these laboratories, all of which affect design practices: control through temporality; control by alignment with strategic objectives; control through alignment with reference research; control through power dynamics; control by avoiding discussion; control through implicit regulation in positioning; control via innovation concepts or expectations; control due to fear of risk; control through infrastructure; control through perceptions of investment; and control by the projected return on the innovation project. These forms of control are discussed in light of the challenges they pose to design, such as making control mechanisms visible and encouraging dialogical processes; promoting tension between creative freedom and strategic direction; reconciling various control forms in the pursuit of innovation; and addressing control as a restrictive force in innovative design projects.
Keywords: Controle; Design; Inovação organizacional; Laboratório de inovação; Control; Corporate innovation; Innovation lab; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial